Autoguide system for conventional vehicle on highway - Zain, R.M. (EDP Sciences, 2014)
This paper highlights possible development of driver assistance control called AutoGuide system for conventional vehicle. The basic aim is to simulate the AutoGuide system which helps the conventional vehicle to be maneuvered on highway. The system is simulated using MATLAB SIMULINK software which accommodate the control of the vehicle steering and vehicle speed. The results are presented in five case studies: 1) Straight road condition, 2) Curve road condition, 3) Ramp road condition, 4) Sharp corner road condition and 5) Road with small to large size foreign object. It is shown that the system give expected responses. Â© 2014 Owned by the authors, published by EDP Sciences.